Photothermal Detection of MicroRNA Using a Horseradish Peroxidase-Encapsulated DNA Hydrogel With a Portable Thermometer - Liu, Xiujuan; Zhang, Meixiang; Chen, Ze; Cui, Jiuqing; Yang, Long; Lu, Zihe; Qi, Fang; Wang, Haixia (Frontiers in Bioengineering and Biotechnology, 2021)
MicroRNA (miRNA) detection has attracted widespread interest as a tumor detection marker. In this work, a miRNA-responsive visual and temperature sensitive probe composed of a horseradish peroxidase (HRP)-encapsulated DNA hydrogel was designed and synthesized. The biosensor converted the miRNA hybridization signal to a photothermal effect which was measured using a digital thermometer. The substrate DNA linker strand of the hydrogel hybridizes with different sequences of miRNA resulting in the collapse of the hydrogel and the release of HRP. HRP oxidizes 3,3’,5,5’-tetramethylbenzidine (TMB) resulting in a color change and a strong photothermal effect was observed after shining near-infrared light on the oxidized product. The thermometer-based readout method has a wide linear range (0.5−4.0 µM) and a limit of detection limit of 7.8 nM which is comparable with traditional UV-vis absorption spectrometry detection and quantitative real time polymerase chain reaction methods. The low cost, ease of operation, and high sensitivity shows that this biosensor has potential for point-of-care biomolecular detection and biomedical applications.